Efficiency tests on Stowe motor - Lawson, Lorin Wendell; Lupfer, James A.; Cassell, Robert Archer (My University, 1907)
Introduction: In the whole field of machinery operation no subject is receiving so much attention today as that of driving by electric motors. It shall be our aim to treat, briefly, several classes of motors; but to show that the Stowe motor is the best type of Shunt Motors. We will start by giving the principle, operation, and use of Shunt Motors in general. Shunt Motors are composed of Field Poles, Armatures, the necessary frame work, commutator, and brushes. The field being wound with a large number of turns of small wire, while the Armature is wound with either Drum or Gramme Ring. The effect of current in the field and Armature causes a skewing of the lines of flux, causing what is known as "cross turns" and "back turns" in the Armature. The cross turns on the Armature tend to change distribution of lines of force on the role faces, skewing them over from trailing tip to entering tip in the case of a motor. To avoid piling up of these lines of force it is necessary to increase the magnetic resistance of the air gap or equivalent at the sides of the pole pieces, or by increasing the air space under the corners.
Citation: Lawson, Lorin Wendell, Lupfer, James A., and Cassell, Robert Archer. Efficiency tests on Stowe motor. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Stowe Motor; Efficiency Testing; Mechanical Engineering; Dynamics; Theses